BELENGGU BUDAYA PATRIARKHI TERHADAP RELASI GENDER DALAM MEMBENTUK KELUARGA sAKINAH - Annisya Maharani; Ulumuddin Ulumuddin; Mufidah Cholil (An Natiq, 2023)
This article discusses the patriarchal shackles of gender relations in its efforts to form a sakinah family. The purpose of this writing is to detect the existence of patriarchal culture in society and then provide understanding and knowledge of the negative impact of patriarchal shackles on gender relations in the family, With this research, it is hoped that it can provide benefits and insight into modern thinking patterns or those that will be applied in the form of writing scientific papers. The method used in this research is literature review with a qualitative approach, pengkajian dalam penelitian ini dilakukan dengan cara mengumpulkan beberapa literatur dan rujukan yang memiliki keterkaitan dengan pembahasan dalam penelitian ini, so that it will produce harmony and obtain accurate data. The results of this study explain the influence of (1) patriarchal culture on gender relations in the family, which results in gender discrimination and limited space for certain genders, and (2) consequences of a patriarchal culture will lead to subordination, marginalization, stereotypes, double burden and violence. This article also explains about patriarchal culture in the view of Islamic law and positive law.